MALHERBE, Janie A. Inventory of documents - MALHERBE, Janie A. (ARCA, 2018)
Private papers of J.A. Malherbe, daughter of Rev. Paul Nel; wife of Dr. E.G. Malherbe
COVERAGE 1850-1970; 9 Files; 0.44 metre
Keywords: MALHERBE, Janie A.; Inventories